DETERMINATION OF TECHNOPARK ACTIVITY BY REGULATORY AND LEGISLATIVE ACTS - Nikolay S. Novikov; Irina V. Karpova (Russian Studies in Law and Politics)
Relevance. Technoparks are one of the most important ways to form a partnership between the state, business, science and education. This voluntary union, on the one hand, arises on the initiative of any of the subjects of the partnership and this active subject carries out a preliminary examination of possible participants in joint activities, assuming that they already have an interest in the declared subject of interaction, or is convinced that in order to solve the problem of interest to him, it is necessary to expand the search for possible partners. The preliminary discussion of joint activities is framed in the form of a project, which is determined by the innovative nature of the future interaction. However, in order to start joint activities of the future team, it is necessary to work out in advance the legislative framework that ensures the legitimacy of future actions of the partnership entities. It is clear that the source of this kind of legislative foundation is the state. If, during the preliminary examination, such moments are discovered, the implementation of which requires further expansion of the legislative framework, the partnership acts as a customer applying to the state body with an initiative to expand the legislative framework. As stated in the normative legal acts, in order to create the necessary regulatory framework corresponding to the type of activity of partner organizations, it is necessary to have a clear definition of such an organization, taking into account its specific features that determine its structure, goals and participants. Therefore, it is important to clarify the concept of a technopark. In the regulatory framework, we are talking about industrial parks, but in accordance with the explanations offered in the regulatory legal acts, such remarks should also be attributed to technoparks as more complex organizations of partner activity: «It was difficult to call such sites industrial parks, since at that time there was not even a terminological unity in the concept of «industrial park», not to mention determining the compliance of a legal entity with the criteria of an industrial park management company, typologies of industrial parks and minimum requirements for the site itself. The development of a regulatory framework is important for any branch of the economy. Without the formalization and institutionalization of economic phenomena, the emergence of state support measures, the evaluation of performance and the creation of development strategies are impossible» [14, p. 6].